Effect of ERAS Baduancao based on the integration of martial arts and medicine on perioperative negative emotion and sleep quality in patients undergoing surgery for gastrointestinal cancer (基于“武医融合”思想的加速康复八段操对胃肠癌患者围手术期负性情绪和睡眠质量的影响) - CAI Hui (蔡晖); ZHOU Chen (周晨); WANG Qing (王青); QIN Mengying (秦梦颖); WANG Yan (王艳) (中西医结合护理)
Objective To evaluate the effect of integrating fitness qigong into ERAS surgery to improve perioperative psychological health and sleep quality in patients with gastrointestinal cancer. Methods Based on the integration of martial arts and medicine, combined with the theory of fitness qigong and the concept of ERAS, the ERAS Baduancaoe was developed through clinical practice. A Total of 78 patients with gastrointestinal cancer admitted from March 2020 to June 2023 were selected as the research subjects. They were randomly divided into a control group of 39 cases and an experimental group of 39 cases using a random number table method. The control group received routine ERAS during the perioperative period, while the experimental group underwent the ERAS Baduancao on this basis. The anxiety status of patients was evaluated using the Self Rating Anxiety Scale (SAS), and sleep quality was observed using wearable smart monitoring devices and the Pittsburgh Sleep Quality Index(PSQI)scale. The perioperative anxiety status and sleep quality of the two groups of patients were compared. Results There were 9 patients lost to follow-up in the experimental group and 8 patients lost to follow-up in the control group. There was no statistically significant difference in SAS and PSQI scores between the two groups of patients before intervention (P>0. 05). The SAS score decreased in both two groups after intervention, and SAS score of patients in the experimental group were lower than that in the control group(P＜0. 05). The results of the two sleep monitoring methods for the two groups of patients were consistent. The overall PSQI score of patients in the experimental group was lower than that in the control group P＜0. 05). The sleep quality monitoring results by intelligent device indicated a superior sleep quality(P＜0. 05) and longer deep sleep duration(P＜0. 01) in the experimental group compared with those in the control group. There was no significant difference in the incidence of postoperative falls, anastomotic bleeding, and development of lower extremity deep vein thrombosis between two groups (P>0. 05). Conclusion The implementation of the baduancao exercise to accelerate recovery in patients with gastrointestinal cancer can relieve perioperative anxiety, improve sleep quality, and accelerate recovery, which is safe and feasible, and can be used clinically. (目的 评价健身气功融入加速康复外科改善胃肠癌患者围手术期负性情绪和睡眠质量的效果。方法 基于“武医融合”思想, 结合健身气功理论及加速康复外科理念, 通过江苏省中医院普外科临床护理实践, 形成加速康复八段操。选取2020年3月—6月收治的78例胃肠癌患者为研究对象, 随机数字表法分为对照组39例和试验组39例。对照组围手术期给予常规加速康复外科措施, 试验组在此基础上实施加速康复八段操。采用焦虑自评量表(SAS)评估患者焦虑状态, 穿戴式智能监测设备及匹兹堡睡眠质量指数(PSQI)量表观察睡眠质量, 比较两组患者围手术期焦虑状况及睡眠质量。结果 对照组脱落8例, 试验组脱落9例。最终对照组31例和试验组30例患者纳入统计。干预前, 两组患者SAS、PSQI量表评分差异无统计学意义(P＞0. 05)。干预后, 两组SAS评分较干预前下降, 且试验组SAS评分改善优于对照组, 试验组焦虑程度低于对照组(P＜0. 05)。两组患者PSQI量表和智能手表两种睡眠监测方式结果一致, 干预后试验组PSQI总评分低于对照组, 差异有统计学意义(P＜0. 05); 智能监测睡眠质量试验组优于对照组(P＜0. 05), 其中深睡眠时长试验组优于对照组(P＜0. 01)。术后跌倒、吻合口出血、下肢深静脉血栓等并发症发生率两组差异无统计学意义(P＞0. 05)。结论 胃肠癌患者实施加速康复八段操, 能改善围手术期焦虑状态, 提高睡眠质量, 加速患者康复, 且安全、可行, 值得临床借鉴推广。)